Antibiotic prescription: An oral physician's point of view - Mahendra Patait; N Urvashi; M Rajderkar; S Kedar; Kinjal Shah; Reeta Patait (Wolters Kluwer Medknow Publications, 2015)
Background: Antibiotics are important in the management and prophylaxis of infections in patients at a risk of experiencing microbial disease. Uses of systemic antibiotics in dentistry are limited since management of acute dental conditions is primarily based upon extraction of teeth or extirpation of the pulp. However, the literature provides evidence of inappropriate prescribing practices by practitioners, due to a number of factors from inadequate knowledge to social factors. Aim: The aim was to assess the therapeutic prescription of antibiotics in the dental office. Materials and Methods: In the current study, 42 faculty members of two dental colleges in the same vicinity were included. A questionnaire was drafted and sent to the dentists to collect data pertaining to the conditions in which antibiotics were prescribed and most commonly prescribed antibiotic. Results: During the study period, 42 faculty members from various departments in the institutes were surveyed, of which 41 questionnaires were completely filled. Amoxicillin was the most commonly prescribed antibiotic followed by other amoxicillin combinations; Metronidazole was most widely prescribed antibiotic for anaerobic infections. Conclusion: We have entered an era where cures may be few due to increasing microbial resistance. The biggest force for change will be if all practicing dentists looked at their prescribing and made it more rational.